Perencanaan dan Perancangan Perpustakaan Harapan Indah dengan Konsep Green Architecture dengan Penekanan pada Efisiensi dan Konserasi Energi - Miarsono, Harry; Putri, Isria Miharni Maherti; Shielvie, Shielvie (Jurnal Pelita Teknologi, 2021)
The increasing energy demand in Indonesia is not matched by a sufficient energy supply. In efforts to support the current condition of the earth, energy efficiency and conservation need to be implemented. Energy efficiency and conservation involve efforts to save energy in buildings and areas. The infrastructure built must meet energy-saving principles, such as hotels, apartments, residential areas, and libraries. Harapan Indah is a residential area located in Bekasi City, specifically in the Medan Satria District. The numerous schools and universities require spaces for students to conduct informal learning activities outside of school and campus. Considering this need, the planning and design of a public library that can accommodate activities for various age groups in the community were undertaken. Harapan Indah Library is designed using the green architecture concept, which emphasizes energy efficiency and conservation with several technologies such as the use of solar panels, roof garden utilization, garden reduction, and maximizing natural lighting and ventilation.